Identification of Stable Potato Varieties from Exotic Sources for Table and Processing Purposes in Bangladesh (SAARC Journal of Agriculture, 2022)
Seven exotic varieties of advanced generation (Cimega, Farida, Jelly, Memphis, Panamera, Taisiya and 7four7) along with four checks (BARI Alu-7, BARI Alu-13, BARI Alu-25 and BARI Alu-28) of potato were evaluated at five agro-ecological locations of Bangladesh during 2016-17 to identify stable varieties for table and processing purposes. Results indicated significant variation among the varieties and locations. To identify the early bulking varieties, tuber yield at 65 DAP was recorded, which showed that the variety 7four7 gave maximum yield (28.1 t ha-1). So, it can be selected as an early market variety. The maturity period of the varieties varied from 85 to 95 days. At the final harvest (95 DAP), the highest average yield over location was also produced by 7four7 (38.7 t ha-1). The varieties Cimega and Memphis also gave comparable yields to that of 7four7 (37.3 and 36.7 t ha-1, respectively). Farida was found suitable for table purposes because of its high yield, medium-sized tubers, oval and smooth shape and good eating qualities. These four varieties were significantly better than the checks in yield. The variety Taisiya produced tubers with good size and shape but low in dry matter content. Memphis produced maximum large-sized tubers, and so it may be suitable for processing. All the varieties produced good dry matter (18-20%). From the AMMI stability analysis, Cimega and 7four7 were the most stable varieties. Taisiya and Memphis were found as medium stable. Based on the stability, tuber yield and other characters, these four varieties may be selected for further studies in the RYT before release as specific purpose varieties.SAARC J. Agric., 19(2): 27-36 (2021)